Arbuscular mycorrhizal fungi contribute to reactive oxygen species homeostasis of Bombax ceiba L. under drought stress - Li, Zhumei; Zhang, Yanan; Liu, Chao; Gao, Yong; Han, Lihong; Chu, Honglong (Frontiers in Microbiology, 2022)
Drought stress is one of the major abiotic factors limiting plant growth and causing ecological degradation. The regulation of reactive oxygen species (ROS) generation and ROS scavenging is essential to plant growth under drought stress. To investigate the role of arbuscular mycorrhizal fungi (AMF) on ROS generation and ROS scavenging ability under drought stress in Bombax ceiba, the ROS content, the expression levels of respiratory burst oxidase homologue (Rbohs), and the antioxidant response were evaluated in AMF and NMF (non-inoculated AMF) plants under drought stress. 14 BcRboh genes were identified in the B. ceiba genome and divided into five subgroups based on phylogenetic analysis. The effect of AMF on the expression profiles of BcRbohs were different under our conditions. AMF mainly downregulated the expression of Rbohs (BcRbohA, BcRbohD, BcRbohDX2, BcRbohE, BcRbohFX1 and BcRbohI) in drought-stressed seedlings. For well-water (WW) treatment, AMF slightly upregulated Rbohs in seedlings. AMF inoculation decreased the malondialdehyde (MDA) content by 19.11% and 20.85%, decreased the O2·- production rate by 39.69% and 65.20% and decreased H2O2 content by 20.06% and 43.21% compared with non-mycorrhizal (NMF) plants under drought stress in root and shoot, respectively. In addition, AMF inoculation increased the non-enzymatic antioxidants glutathione (GSH) and ascorbic acid (AsA) content in roots by 153.52% and 28.18% under drought stress, respectively. The activities of antioxidant enzymes (SOD, PX, CAT, APX, GPX, GR, MDAR and DHAR) all increased ranging from 19.47% - 131.54% due to AMF inoculation under drought stress. In conclusion, these results reveal that AMF inoculation can maintain ROS homeostasis by mitigating drought-induced ROS burst, via decreasing ROS generation and enhancing ROS scavenging ability of B. ceiba seedlings.